In Pursuit of the Parietal Cell – An Evolution of Scientific Methodology and Techniques - Baratta, Vanessa; Own, Jason; Di Renzo, Chiara; Ollodart, Jenna; Geibel, John P.; Barahona, Maria (Frontiers in Physiology, 2019)
The stomach has unique embryologic and anatomic properties, making the study of the parietal cell technically challenging. Numerous individuals have devoted decades of research to unraveling the pathophysiological basis of this cell type. Here, we perform a scoping review of novel in-vitro and in-vivo methodology pertaining to the parietal cell. First, we evaluate early in-vitro methods of parietal cell analysis. This section focuses on three major techniques: gastric gland isolation, parietal cell isolation, and parietal cell culture. Second, we discuss more contemporary efforts involving confocal microscopy and gastric organoids, a new technique that holds much promise in unveiling the temporal-spatial dynamics of the cell. Finally, we will discuss findings from our laboratory where we identified an active gastric vacuolar H-ATPase as a putative mechanism for refractory GERD. Overall, this review aims to highlight the major milestones in understanding an elusive yet important cell. Though in no way comprehensive, we hope to provide a birds-eye view to the study of this unique cell type in the gastrointestinal tract.